พฤติกรรมเสาเข็มเจาะที่ใช้สารละลายโพลิเมอร์เป็นสารรักษาเสถียรภาพหลุมเจาะในชั้นดินกรุงเทพฯ - วุฒิชัย ชื่นหิรัญ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The polymer based slurry is recently used as the hole stabilized fluid during construction of wet process bored pile in Bangkok. The bentonite slurry creates a thick cake film during bored pile construction and reduce the skin friction as well as end bearing capacity of the bored pile. The polymer slurry shows the advantage in increasing of not only skin friction but also end bearing capacity of pile compared to using bentonite slurry. This research aims to verify the adhesion factor(α),friction factor (β) and Nq parameters for estimating bored pile capacity. The data of pile load tests with fully instrumentations were collected in the past 10 years for estimated the α, β and Nq value as well as the pile displacement in each soil layers. Load transfer was carefully considered based on stress strain relationship with fully mobilization stage. The designed parameters of α, β and Nq are proposed in terms of undrained shear strength of clay and angle of friction of sand. The approach for prediction of pile capacity and settlement of pile is also discussed and presented.